Globalization, modernity, and migration: The changing visage of social imagination - ESPENA, Darlene Machell (Institutional Knowledge at Singapore Management University, 2011)
In this article, I assert that the recent phenomenon of migration is one apparent and fundamental process that shapes human communities, transforming cultural variation, and distorts the constructs of distance and space. The boundaries of nation-states and identities are constantly being challenged, restructured and interrogated and the trends of modernity and globalization, new ways of projecting feelings and diffusing cultures among displaced communities are produced. The article looks for the new stories that are produced with this vibrant intersection of globalization, modernity and migration. In particular, I focus on the distinct Sikh migrant community in the Philippines: how they have evolved, how the forces of globalization have pervaded their lifestyle and how they have utilized the benefits of recent trends of modernity to survive life beyond India’s borders. I maintain that Sikh migrants choose to stay in the Philippines because they have produced a simulation of life in their home country albeit with perceptible deviations. This transplanted community utilized the benefits of globalization and modernity to modify the limited space they occupy to re-create their homeland and therefore India has been easier to “imagine,” “visualize” and “experience.”